Ventriculer fibrillation due to Prinzmetal angina in a pregnant patient - Ahmet Gündeş; Ahmet Çelik; İsmail Türkay Özcan; Ahmet Çamsarı (KARE Publishing, 2015)
Variant angina, which is also referred to as prinzmetal or coronary vasospastic angina, is a clinical entity characterized by episodes of angina pectoris, usually at rest and often between midnight and early morning, in association with ST-segment elevation on the electrocardiogram. Angina is usually caused by focal spasm of a major coronary artery resulting in a high-grade obstruction, and myocardial infarction may develop in some cases. We report a prinzmetal angina which caused ventricular fibrillation and cardiac arrest in an 18-week pregnant woman.